GENETIC TRANSFER OF STREPTOMYCIN AND AMINOPROPANOLSTREPTOMYCIN RESISTANCE - Von Graevenitz, Alexander (1964)
von Graevenitz, Alexander (Yale University, New Haven, Conn.). Genetic transfer of streptomycin and aminopropanolstreptomycin resistance. J. Bacteriol. 88:960–964. 1964.—Transduction and conjugation experiments with Staphylococcus aureus and Escherichia coli suggest that resistance to streptomycin (S) and aminopropanolstreptomycin (A) is due to the same mutation arising in a single step at the locus str. The high occurrence of S(r)A(s) cells (1 to 3%) in an S(r)A(r) population was noted. From genetic crosses of S(r)A(s) with S(s)A(s) cells, it can be concluded that there is a suppressor locus su-A adjacent to, but separable by recombination from, the str locus. It modifies the genotype S(r)A(r) to the phenotype S(r)A(s).